2015
DOI: 10.3233/sw-140142
|View full text |Cite
|
Sign up to set email alerts
|

Resource-constrained reasoning using a reasoner composition approach

Abstract: To increase the interoperability and accessibility of data in sensor-rich systems, there has been a recent proliferation of the use of Semantic Web technologies in sensor-rich systems. Quite a range of such applications have emerged, such as hazard monitoring and rescue, context-aware computing, environmental monitoring, field studies, internet of things, and so on. These systems often assume a centralized paradigm for data processing, which does not always hold in reality especially when the systems are deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Consequently, Tai et al [48] describe a "selective rule loading" algorithm to determine this ruleset. As a type of naïve forward-chaining algorithm, it executes each rule sequentially on the initial dataset, adding any inferences.…”
Section: Domain-based Ruleset Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, Tai et al [48] describe a "selective rule loading" algorithm to determine this ruleset. As a type of naïve forward-chaining algorithm, it executes each rule sequentially on the initial dataset, adding any inferences.…”
Section: Domain-based Ruleset Selectionmentioning
confidence: 99%
“…Implementing and benchmarking this as an optimization for all rules is considered future work. Tai et al [48] propose a selective rule loading algorithm, which composes an OWL2 RL ruleset depending on the input ontology. In our benchmarks, we found that this domain-based rule selection can significantly improve performance.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations